Buya, Surau, and Lapau: Mahyeldi Ansharullah's Identity Politics Propaganda in Digital Space - Afandi, Yusuf; Daulay, Zainul; Rais, Zaim (Universitas Muhammadiyah Yogyakarta, 2025)
This article aims to analyze the identity politics propaganda strategy used by Mahyeldi in the 2024 regional head elections through his official Instagram account, @mahyeldisp. The theory used in this article is the propaganda theory by Decker which comprehensively highlights the symbols of religion and Minangkabau culture - Buya, Surau and Lapau - represented to build a strong identity politics image. These three symbols are used as political ideals that are identical to Minangkabau culture which is closely related to the collaboration between religion and culture as a philosophy of life. This writing uses a content analysis approach to uploads, use of symbols, diction, and hashtags on the Instagram account @mahyeldisp during the 2024 regional election campaign period. The results of this study indicate that the @mahyeldisp account is used as a means of strengthening Islamic narratives framed by Minangkabau traditional values, as well as forming a new image as a figure close to millennials. Buya, which is a symbol for a respected religious figure, as a means of strengthening his Islamic identity, Surau as a symbol of the closeness of religion and customs that builds the religiosity of society, and lapau as an arena for discussion and a space for dialectics of the Minangkabau people are used to strengthen their figures to influence voters. This finding strengthens the narrative of the importance of identity politics propaganda by collaborating cultural and religious values in influencing voters' political choices, especially in digital media.